Association of in-hospital intensive statins dosage and death in arteriosclerotic cardiovascular disease with percutaneous coronary intervention: insights of multicentre cohort from China - Chen, Peng-yuan; Liu, Yuan-hui; Duan, Chong-yang; Fan, Hua-lin; Zeng, Li-huan; Guo, Wei; Jiang, Lei; Wei, Xue-biao; He, Wen-fei; Tao, Sha; Guo, Zhi-qiang; Chen, Ji-yan; et al. (European journal of clinical pharmacology, 2020)
Purpose In-hospital statin dosage-related effect remains unknown for patients with arteriosclerotic cardiovascular disease (ASCVD). This study aimed to determine the associations of different in-hospital intensive statins dosages with the prognosis for patients in the era of percutaneous coronary intervention (PCI). Methods From January 2010 to December 2014, consecutive ASCVD patients receiving PCI were enrolled from five centres in China. All the enrolled patients were classified into high-dose (40 mg atorvastatin or 20 mg rosuvastatin) or low-dose (20 mg atorvastatin or 10 mg rosuvastatin) intensive statin group. In-hospital all-cause death was the primary outcome. Results Of the 7008 patients included in this study, 5248 received low-dose intensive statins (mean age, 64.28 ± 10.39; female, 25.2%), whereas 1760 received high-dose intensive statins (mean age, 63.68 ± 10.59; female, 23.1%). There was no significant difference in the in-hospital all-cause death between the two groups (adjusted OR, 1.27; 95% CI, 0.43–3.72; P = 0.665). All-cause death was similar between the two groups during the 30-day follow-up period (adjusted HR, 1.28; 95% CI, 0.55–2.97; P = 0.571). However, the high-dose intensive statins were tightly associated with the reduction in in-hospital dialysis (adjusted OR, 0.11; 95% CI, 0.01–0.81; P = 0.030). Besides, primary analyses were confirmed by subgroup analyses. Conclusions The in-hospital high-dose intensive statins are not associated with the lower risk of in-hospital or 30-day all-cause death among ASCVD patients undergoing PCI. Given the robust beneficial effect of high-dose intensive statins with in-hospital dialysis, an individualized high-dose intensive statin therapy can be rational in specified populations.